THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT REGIONAL SECRETARIAT - sariya; Ellin Herlina; Mahfud (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — This study aims to obtain empirical evidence about the influence of variables Influence of Leadership Style, Work Motivation and Organizational Culture on Employee Performance and want to know the dominant variable influence on Employee Performance at the Regional Secretariat of Cirebon Regency. Research method—The research population is 37 people, namely all employees. The method used is descriptive analytic and the nature of the research is explanatory. While the data analysis using multiple regression analysis. Result— For testing the research hypothesis simultaneously, the F test is used and for partial hypothesis testing, the t test is used. The results showed that the leadership style variable simultaneously had a significant effect on employee performance. The magnitude of the simultaneous influence is 0.635 or 63.5% is the contribution of leadership style to employee performance, work motivation has a significant effect on employee performance. The magnitude of the simultaneous influence is 0.710 or 71% is the contribution of work motivation to employee performance and Organizational Culture has a significant effect on employee performance. Conclusion— The magnitude of the simultaneous influence is 0.793 or 79.3% is the contribution of organizational culture to employee performance. Partially, leadership style, work motivation and organizational culture have a significant effect on employee performance. The magnitude of the direct partial effect of leadership style, work motivation and organizational culture significantly influence employee performance is 0.807 or 80.7%. Thus, the performance of employees carried out by employees of the Cirebon Regency Regional Secretariat was obtained by 80.7%.